The "Muaro-Pekanbaru" Railway Monument Cultural Reserve as a Source For Local History Learning in Pekanbaru - Piki Setri Pernantah; Rizki Ananda Hasibuan; Hana Puspita Sari; Rahmi Adisti; Sony Setiawan; Apriani Ladita (Tarikhuna: Journal of History and History Education, 2023)
Local history learning can be used to foster students' awareness and interest in the area where they live. Through learning local history students can also learn about the uniqueness of their region such as culture, historical heritage and local wisdom. One source that can be used as a local history lesson is the "Muaro-Pekanbaru" Railway Monument cultural reserve. This monument is a historical heritage located in Pekanbaru City, Riau Province and is one of the proofs of the Japanese occupation of Indonesia when they occupied Pekanbaru. The existence of this railway monument was built to commemorate and honor the romushas who died tragically in the construction of a train network that connected the east coast and west coast of Sumatra with the route from Muaro to Pekanbaru. This monument can be a source of learning local history for the community, especially in Pekanbaru. This paper aims to explain the utilization of the "Muaro-Pekanbaru" Railway Monument Cultural Heritage Site in learning local history. The approach used in this study is descriptive-qualitative. The results of the study show that the "Muaro-Pekanbaru" Railway Monument cultural heritage can be used as a source of learning local history in Pekanbaru.